A New Era in Cancer Care: How a Five-Minute Jab is Revolutionizing Treatment - Elayedath, Rajesh; Naja, Fathima (Nepal Journal of Epidemiology, 2025)
As there is an increased prevalence of cancer, healthcare systems must accommodate the growing number of patients without placing extra pressure on resources. If the NHS adheres to evidence-based, patient-led, and cost-effective modifications, the five-minute injection can represent the initiation, not only of a new era in cancer care, but also of an era of flexibility, humanity, and sustainability in the public health sector.